Toxoplasma gondii And Neospora caninum In Brain Tissue Of Rodents In North-West Iran - Nazari N (Dove Medical Press, 2019)
Naser Nazari,1 Saeedeh Shojaee,2 Mehdi Mohebali,2 Aref Teimouri,2,3 Keyghobad Ghadiri,4 Saber Raeghi,5 Mohammad Reza Shiee,2,3 Yousef Azarakhsh,6 Arezoo Bozorgomid4 1Department of Medical Parasitology and Mycology, School of Medicine, Kermanshah University of Medical Sciences, Kermanshah, Iran; 2Department of Medical Parasitology and Mycology, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran; 3Students Scientific Research Center, Tehran University of Medical Sciences, Tehran, Iran; 4Infectious Diseases Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran; 5Department of Laboratory Sciences, Maragheh University of Medical Sciences, Maragheh, Iran; 6Department of Biology, Razi University, Kermanshah, IranCorrespondence: Arezoo BozorgomidInfectious Diseases Research Center, Kermanshah University of Medical Sciences, Kermanshah, IranTel +98 918 872 8269Email arezoobozorgomid@yahoo.comPurpose: Rodents live in proximity to humans and domestic animals. These creatures can serve as reservoir hosts for many zoonotic parasites; therefore, they increase the risk of human infections. The aim of this study was to investigate Toxoplasma gondii and Neospora caninum in rodents caught in Meshgin-Shahr District, Iran.Patients and methods: In a cross-sectional study, brain samples were collected from 70 rodents caught in Meshgin-Shahr District during March and December 2015. The specimens were examined for exposure to T. gondii and N. caninum with molecular methods.Results: Seventy rodents were caught, including 50 Meriones persicus, 11 Mus musculus and 9 Cricetulus migratorius. Thirty rodents were female and 40 were males. Using PCR (B1 gene), T. gondii was detected in 7.1% (5/70) of the rodents while N. caninum was not detected. The prevalence of Toxoplasma infection was higher in female rodents (4.28%) compared to male rodents (2.86%), but the difference was not significant.Conclusion: The results showed a low risk of T. gondii and N. caninum among rodents. Finally, further research is needed to understand the role of these rodent species in the transmission of the above protozoan pathogens to humans and livestock in this area.Keywords: rodents, Neospora, Toxoplasma, prevalence, PCR, Iran